Evaluating sedimentary PAH bioavailability based on equilibrium partitioning and passive sampling at the Dover Gas Light Superfund Site (Dover, Delaware, USA). (25th May 2021) - Burgess, Robert M.; Grossman, Scott; Ball, Gerald; Kady, Thomas; Sprenger, Mark; Nevshehirlian, Stepan
Abstract: From 1859 to 1948, the Dover Gas Light plant produced combustible gas for industrial, commercial, and residential applications using pine resin, coking coal, oil, and wood, and finally, a coal–gas process. Waste coal tar was discharged into the St. Jones River in Dover, Delaware (USA), via a ditch and culvert and, following plant closure in the 1940s, through groundwater flow from structures buried on the site. By the end of the 20th century, polycyclic aromatic hydrocarbon (PAH) contamination of the sediments in the St. Jones River was suspected to have occurred, and state and federal agencies initiated environmental assessments of the newly designated Superfund site. The current study investigated the spatial distributions of total PAHs in St. Jones River sediments adjacent to the site and evaluated their bioavailability. In 2017, 34 sediment cores were collected, sectioned, and analyzed using an on‐site fluorometric screening technology indicating total PAH sediment concentrations ranging from 0.1 to 15 000 mg/kg (wet). A subset of cores involving 20 samples of various depths was selected and further analyzed by conventional GC/MS analysis for 16 parent PAHs. In addition, a 34‐day in situ deployment of polyethylene passive samplers was performed to measure vertical bioavailability profiles of parent PAHs in sediments at three locations and overlying waters at four stations. Freely dissolved concentrations ( C free ) of total PAHs were estimated based on equilibrium partitioning (EqP) of the GC/MS results and the passive sampling findings. C free values were used to calculate acute and chronic toxic units ranging from 1.4 to 56, based on EqP and 1.3 to 15 based on passive sampling. For six samples where comparative data were available, EqP calculations overestimated bioavailability by < 2‐ to 54‐fold. Combining rapid field measurements with more accurate analyses of sediment concentrations and bioavailability in a tiered framework supported a time‐efficient and cost‐effective site investigation. Integr Environ Assess Manag 2021;17:1215–1228. © Published 2021. This article is a U.S. Government work and is in the public domain in the USA. KEY POINTS: Applied a combination of screening technology, analytical analyses, and passive sampling to assess a sediment site contaminated with polycyclic aromatic hydrocarbons (PAHs). Equilibrium partitioning (EqP) and passive sampling used to determine and compare freely dissolved concentrations ( C free ) and toxic units. Tiered approach provided time‐ and cost‐effective and scientifically robust decision‐making framework.